Physical exercise for treating non-motor symptoms assessed by general Parkinson’s disease scales: systematic review and meta-analysis of clinical trials - Valton Costa; Alice de Oliveira Barreto Suassuna; Thanielle Souza Silva Brito; Thalita Frigo da Rocha; Anna Carolyna Gianlorenco (BMJ Neurology Open)
Introduction Parkinson’s disease is a movement disorder that also manifests non-motor symptoms (NMS). Physical exercise is a prominent strategy that can have an impact on NMS; however, the evidence is limited. Our aim was to verify the effects of exercise on NMS, as assessed using general NMS scales.Methods This study is a systematic review and meta-analysis. Two searches were conducted on the PubMed, Cochrane Library, Scopus, Web of Science, Embase, Science Direct and PEDro databases from September to December 2022. The PEDro scale was used to assess the methodological quality of the studies.Results Twenty-three studies were included. The interventions were classified as multimodal, aerobic, resistance, dance, conventional physical therapy and other types. Five studies had high risk of bias. Eight studies were included in the meta-analyses. According to the criteria, four studies compared exercise with non-exercise (n=159), two compared multimodal exercise with cognitive/leisure approaches (n=128), and two compared aerobic with conventional exercise (n=40). No statistical differences were observed between exercise and non-exercise (−0.26 (−0.58 to 0.05)) and between multimodal and cognitive approaches (0.21 (−0.14 to 0.55)). However, trends were observed in the direction of exercise and cognitive approaches. A significant difference was observed favouring aerobic over conventional exercise (−0.72 (−1.36 to −0.08)).Conclusions Our findings suggest that exercise may have an effect on general NMS compared with non-exercise, although only a trend was observed. It was also observed for cognitive approaches over multimodal exercises. Aerobic exercise showed near-large effects compared with conventional exercise.